CREATION OF SUPPLY CHAIN MANAGEMENT AIMED AT IMPROVING THE QUALITY AND ACCESSIBILITY OF MUNICIPAL SERVICES - Rudnev, Alexander V.; Duborkina, Irina A.; Barmenkova, Natalya A.; Boyko, Alexey N.; Sanginova, Lola D. (International Journal of Supply Chain Management, 2020)
Abstract? Supply chain management of regulation are mainly used in the field of municipal services management. Coordination between local governments and other organizations that control the provision of municipal services is poorly developed on the territory of municipal entities. The solution to this problem becomes particularly relevant in the context of creating the supply chain system for the management. It is quite obvious that a review of approaches and methods in organizing the provision of municipal services is necessary under supply chain strategy. First of all, we implemented the effective supply chain for allocation of resources in the context of the transition to medium-term budget planning, and also to the integration of supply chain mechanism for organizing the provision of municipal services in the existing territorial development management system. This article provides an insight into supply chain management practices in a municipal context. It highlights the status, challenges and way forward for the implementation of supply chain management in a municipal environment.